Improving Access to European E-theses: the DART-Europe Programme - Moyle, Martin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
DART-Europe (Digital Access to Research Theses - Europe) is a partnership of research libraries and library consortia who are working together to improve global access to European research theses. The Programme is endorsed by LIBER (Ligue des Bibliothèques Européennes de Recherche) as part of the work of the LIBER Access Division, and it is the European Working Group of the NDLTD (Networked Digital Library of Theses and Dissertations). DART-Europe serves as a European networking forum on issues relating to electronic theses. The DART-Europe partners share an enthusiasm for open access to research theses, and they have helped to provide researchers with the DART-Europe E-theses Portal, a service which enables the discovery of the open access research-level e-theses offered by institutions and consortia from a growing number of European countries. This article gives an overview of DART-Europe, its progress and its future plans, with particular reference to the DART-Europe E-theses Portal.